Growth kinetics of the filamentous microorganism Sphaerotilus natans in a model system of a food industry wastewater - Contreras, Edgardo Martin (2000)
Bulking by Sphaerotilus natans has been attributed to several factors such as low dissolved oxygen in the aeration basin, wastes with high C:N ratios and phosphorus limitation; however, the occurrence of bulking has been reported in fruit, vegetable, meat and poultry wastewaters in which the ratio C:N is variable. Growth of S. natans was analyzed in a model system of a food industry wastewater (potato processing waste) that was characterized by HPLC determining that citric acid was the most important identified component. The effect of several carbon sources on S. natans growth was also studied; different C:N ratios were tested in a continuous culture system (chemostat). This strain grew in a mineral medium with citric acid as a sole carbon source, in spite of the contradictory results found in literature. Chemostat studies showed that the medium was carbon-limited when C:N ratios <19 mgCOD (mgN-NH3)−1. Monod kinetic growth coefficients, determined for this strain in chemostat were: maximum specific growth rate, μmax=0.301 h−1; Monod constant, KS=4.6 mgCOD l−1; true biomass growth yield, YTX/S=0.490 mgVSS (mgCOD)−1; endogenous decay rate, kd=0.011 h−1 and maintenance coefficient, mS=0.022 mgCOD (mgVSS)−1 h−1. The obtained parameters were compared with literature data and the effect of glucose and citric acid as carbon sources was discussed; these parameters are useful in modeling the growth of S. natans in potato processing wastewaters (or in other effluents under carbon-limiting conditions) especially when citrate is the main component and can be used to control filamentous bulking by metabolic or kinetic selection.